Principles of creation of complex physical rehabilitation program for children after cochlear implantation - Zastavna, O.M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: to elucidate main principles of complex physical rehabilitation program for senior pre-school age children after cochlear implantation. Material: 40 hard hearing children of senior pre-school (main group) were tested. Main group N1 consisted of hard hearing children (10 boys and 11 girls), who did not underwent cochlear implantation and learned by program of pre-school educational establishment for hard-hearing children. Main group N2 consisted of 19 children after cochlear implantation, registered at oral-aural specialists (10 boys and 9 girls). For them the author’s program of physical rehabilitation was worked out. Comparison group consisted of 40 children with normal hearing (18 boys and 22 girls). Effectiveness of the worked out program was assessed by parameters of physical and psycho-motor condition, by children’s physical qualities. Results: the offered program of children’s physical rehabilitation was developed on the base of assessment of physical and psycho-motor condition, physical fitness. The program is of complex character and includes the following elements: domestic habilitation, kinetisotherapy methodic (morning hygienic exercises, Yoga for children, health related training complex, fit-ball training, breathing and articulation exercises), massage (general, speech therapy massage), hardening. Conclusions: Complex character of the worked out program implies diverse influence on different disorders in children’s organisms. All these are realized against the background of main etiological factor of these changes (deafness) removal. Such approach results in improvement of children’s condition, their quicker socialization and possibility to study in comprehensive school in due time.